2014
DOI: 10.1103/physreve.89.032145
|View full text |Cite
|
Sign up to set email alerts
|

Classical scattering in strongly attractive potentials

Abstract: Scattering in central attractive potentials is investigated systematically, in the limit of strong interaction, when large-angles scattering dominates. In particular, three important model interactions (Lennard-Jones, Yukawa, and exponential), which are qualitatively different from each other, are studied in detail. It is shown that for each of these interactions the dependence of the scattering angle on the properly normalized impact parameter exhibits a quasi-universal behavior. This implies simple scaling o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 36 publications
0
56
1
Order By: Relevance
“…It means that this effect makes the phase transition at least weaker. So, as the non-ideality corrections [1,3,4,10] were obtained without taking the effect of the non-linear screening into account, we expect that areas of negative compressibility will be at least smaller as in Diehl et al [13] if one takes this effect into account. Diehl et al also showed [13] that Z * < Z; however, they did not consider how the phase diagram [1] changed if the non-linear screening effect was taken into account like in section 3 (see some explanations in section 2).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It means that this effect makes the phase transition at least weaker. So, as the non-ideality corrections [1,3,4,10] were obtained without taking the effect of the non-linear screening into account, we expect that areas of negative compressibility will be at least smaller as in Diehl et al [13] if one takes this effect into account. Diehl et al also showed [13] that Z * < Z; however, they did not consider how the phase diagram [1] changed if the non-linear screening effect was taken into account like in section 3 (see some explanations in section 2).…”
Section: Introductionmentioning
confidence: 92%
“…It was stressed in Martynova and Iosilevskiy [9] that large regions of negative total pressure and negative total compressibility exist at not too large values of Γ and on the phase diagram [1] as one uses non-ideal corrections P ex (T Z , T i , Z, n Z ) from Hamaguchi et al [1] and Khrapak et al [10] in the total equations of state of a complex plasma:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the Yukawa-like potential is the solution of the PB equation. Such systems are widely known and many references can be cited (see, e.g., [6][7][8][9][10][11] ). However, the linearization condition is invalid for the systems that are considered in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we suppose that the neglect of the non-linear screening is one of the causes of the existence of excessive total negative pressure and total negative compressibility areas [16] in the phase diagram [6] of the complex plasma. These areas were obtained in [16] by means of the equations of state [6][7][8][9]] . We expect that if the non-linear screening effect would be taken into account, then the areas of negative compressibility will be very small in the very least.…”
Section: Introductionmentioning
confidence: 99%